Ixekizumab improves patient-reported outcomes up to 52 weeks in bDMARD-naïve patients with active psoriatic arthritis (SPIRIT-P1). (25th June 2018) - Gottlieb, Alice B; Strand, Vibeke; Kishimoto, Mitsumasa; Mease, Philip; Thaçi, Diamant; Birt, Julie; Lee, Chin H; Shuler, Catherine L; Lin, Chen-Yen; Gladman, Dafna D
Abstract: Objective: To report patient-reported outcomes of patients with PsA treated with ixekizumab up to 52 weeks. Methods: In SPIRIT-P1, biologic-naïve patients with active PsA were randomized to ixekizumab 80 mg every 4 weeks (IXEQ4W; N = 107) or every 2 weeks (IXEQ2W; N = 103) following a 160 mg starting dose, adalimumab 40 mg every 2 weeks (ADA; N = 101) or placebo (PBO; N = 106) during the initial 24-week double-blind treatment period. At week 24 (week 16 for inadequate responders), ADA (8-week washout before starting ixekizumab) and PBO patients were re-randomized to IXEQ2W or IXEQ4W. Patients receiving ixekizumab at week 24 received the same dose during the extension period (EP) to week 52. Patients completed measures including the Dermatology Life Quality Index (DLQI), Itch Numeric Rating Scale, 36-Item Short Form Health Survey version 2, European Quality of Life 5 Dimensions Visual Analogue Scale and Work Productivity and Activity Impairment Questionnaire-Specific Health Problem. Results: The IXEQ4W, IXEQ2W and ADA groups reported significant improvements in DLQI at week 24; 22% (PBO), 53% (IXEQ4W), 63% (IXEQ2W) and 54% (ADA) of patients reported DLQI scores of 0/1. The IXEQ4W, IXEQ2W and ADA groups reported significant improvements in Itch Numeric Rating Scale, 36-Item Short Form Health Survey version 2 physical component summary and some domain scores, and European Quality of Life 5 Dimensions Visual Analogue Scale at weeks 12 and 24; and in three of four Work Productivity and Activity Impairment Questionnaire-Specific Health Problem domains at week 24. Results are also presented through week 52 for the EP. Conclusion: In biologic-naïve patients with active PsA, ixekizumab significantly improved skin symptoms, health-related quality of life and work productivity. Trial Registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT01695239; EU Clinical Trials Register, https://www.clinicaltrialsregister.eu, EudraCT2011-002326-49